Mamá and me - Dorros, Arthur; Gutierrez, Rudy (New York : Rayo, 2011)
A girl and her mother spend a day together gardening, making cookies, and visiting a neighbor. Includes Spanish words interspersed in the text.
2.2
K-3
K-3
Keywords: Mothers and daughters -- Juvenile fiction; Mothers and daughters -- Fiction; Mother-daughter relationship -- Fiction; Picture books for children